Differences in the Cognitive Development of Children Crawl and Don't Crawl - Septi Fitriana (Universitas Syiah Kuala, 2023)
The purpose of this study was to determine the differences in the cognitive development of children who crawled and did not crawl. This research was conducted in July-December 2022. This research method uses qualitative research. Data was collected in this study using observation and documentation. The conclusion of this study is that children who crawl have cognitive development faster than children who do not crawl, because in processing information and doing activities, children who crawl are faster in responding to the information conveyed because the nervous system in their brain is more connected, thereby developing muscle turned out to greatly affect the development of the child's brain.